Subtelomeric proteins negatively regulate telomere elongation in budding yeast - Berthiau, Anne-Sophie (2006)
The Tbf1 and Reb1 proteins are present in yeast subtelomeric regions. We establish in this work that they inhibit telomerase-dependent lengthening of telomere. For example, tethering the N-terminal domain of Tbf1 and Reb1 in a subtelomeric region shortens that telomere proportionally to the number of domains bound. We further identified a 90 amino-acid long sequence within the N-terminal domain of Tbf1 that is necessary but not sufficient for its length regulation properties. The role of the subtelomeric factors in telomere length regulation is antagonized by TEL1 and does not correlate with a global telomere derepression. We show that the absence of TEL1 induces an alteration in the structure of telomeric chromatin, as defined biochemically by an increased susceptibility to nucleases and a greater heterogeneity of products. We propose that the absence of TEL1 modifies the organization of the telomeres, which allows Tbf1 and Reb1 to cis-inhibit telomerase. The involvement of subtelomeric factors in telomere length regulation provides a possible mechanism for the chromosome-specific length setting observed at yeast and human telomeres.